The Pursuit of Reality: Recent Research into the History of Witchcraft - Gaskill, Malcolm (The historical journal, 2008)
In recent years the outpouring of historical work on witchcraft has been prodigious. Twenty-first-century studies encompass every conceivable chronological and geographical area, from antiquity to the present, Massachusetts to Muscovy. Approaches have been varied, with witchcraft explored as an intellectual, legal, political, social, cultural, and psychological phenomenon. Of particular interest – and difficulty – is the ‘reality’ of witchcraft: how historians might recover contemporary meanings, beyond the meanings imposed by rationalists, romantics, and social scientists. This article examines nine books from the last five years to assess the state of the field, and to offer some suggestions for research in the future.